209k views
5 votes
[18].Simplify (TTE): x(2x+y+5) - 2(x²+xy+5) + y(x + y)


1 Answer

4 votes

Answer:


x(2x+y+5) - 2(x\²+xy+5) + y(x + y) = 5x -10 + y\²

Explanation:

Given


x(2x+y+5) - 2(x\²+xy+5) + y(x + y)

Required

Simplify

We have:


x(2x+y+5) - 2(x\²+xy+5) + y(x + y)

Open brackets


x(2x+y+5) - 2(x\²+xy+5) + y(x + y) = 2x\²+xy+5x - 2x\²-2xy-10 + xy + y\²

Collect like terms


x(2x+y+5) - 2(x\²+xy+5) + y(x + y) = 2x\²- 2x\²+xy-2xy+ xy+5x -10 + y\²


x(2x+y+5) - 2(x\²+xy+5) + y(x + y) = 5x -10 + y\²

User PAEz
by
4.6k points